Intervention program efficacy for spelling difficulties - Sampaio, Maria Nobre (2014)
OBJECTIVE:To develop an intervention procedure for spelling difficulties and to verify the effectiveness of the intervention program in students with lower spelling performance.METHOD:We developed an intervention program for spelling difficulties, according to the semiology of the errors. The program consisted of three modules totaling 16 sessions. The study included 40 students of the third to fifth grade of public elementary education of the city of Marilia (SP), of both genders, in aged of eight to 12 years old, being distributed in the following groups: GI (20 students with lower spelling performance) and GII (20 students with higher spelling performance). In situation of pre and post-testing, all groups were submitted to the Pro-Orthography.RESULTS:The results statistically analyzed showed that, in general, all groups had average of right that has higher in post-testing, reducing the types of errors second semiologycal classification, mainly related to natural spelling errors. However, the results also showed that the groups submitted to the intervention program showed better performance on spelling tests in relation to not submitted.CONCLUSION:The intervention program developed was effective once the groups submitted showed better performance on spelling tests in relation to not submitted. Therefore, the intervention program can help professionals in the Health and Education to minimize the problems related to spelling, giving students an intervention that is effective for the development of the spelling knowledge.